The Influence of E-Service Quality on Customer’s E-Loyalty: E-Perceived Value and E-Satisfaction as Mediating Variable - Abror; Sakinah (Marketing Management Studies, 2021)
This study aims to analyze how the influence of e-service quality to e-loyalty on customers of Tokopedia with e-perceived value and e-satisfaction as mediating variable. This research was conducted using quantitative methods. The population of this study is all customers who have visited and shopped at Tokopedia website. The samples were 230 respondents. This study used structural equation model (SEM) as the data analysis tools. The results found that: (1) E-Service quality has a significant direct effect on E-Perceived Value. (2) E-Service Quality has a significat direct effect on E-Satisfaction. (3) E-Perceived Value has a significant direct effect on E-Satisfaction. (4) E-Perceived Value has a significant direct effect on E-Loyalty. (5)E-Satisfaction has a significant direct effect on E-Loyalty (6)E-Service Quality does not have a siginificant direct effect on E-Loyalty. (7) E-Service Quality has a significant indirect effect on E-Loyalty with E-Perceived Value as mediating variable. (8) E-Service Quality has a significant indirect effect on E-Loyalty with E-Satisfaction as mediating variable.